(untitled) (MAUSAM, 1953)
The diurnal variation of II at Huancayo is found to be considerably larger than that expected in such regions. McNish (1937) explained the large variation as follows. According to the dynamo theory the main electrometric forces are induced in middle and higher latitudes, which drive the cur-rent eastwards in low latitudes, where, if the geographic and geomagnetic equators coincide, it is opposed by the electromotive forces induced there, but if the two equators are apart, then in the region between these two, the electromotive forces induced there help the current flow, resulting in its en-hancement. Chakravarty (1946) suggest-ed geomagnetic control of the diurnal varia-tion in low latitudes. Egedal (1947) showed from the data of some stations in and near the equatorial region that the diurnal mag-netic variation was symmetrical about the magnetic equator. He suggested that the augmentation of the range of H in a narrow zone near the magnetic equator might be due to a varying electric current flowing in a very narrow zone of the atmosphere above the magnetic equator at a height of about 100 km. Chapman (1948) found that diurnal variation was large at places near which the magnetic equator crossed the geographic equator at a steep angle and was less at places where the change in the latitude of the magnetic equator was slow. Mart-pi (1949) was of the view that the distribution of diurnal range was symmet-rical about an equator between the mag-netic and geomagnetic equators. He men-tioned that McNish’s theory did not appear to account for the observed effects as al-though it gave approximate symmetry about the magnetic equator it did not ac-count for the large enhancement. He thought that the enhancement was more likely to be due to an increase in conduc-tivity of the ionosphere near the magnetic.